2019
DOI: 10.22146/jpti.35954
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatile Compound at Different Age of Corn Crops Used as Bemisia tabaci Repellent

Abstract: Bemisia tabaci is one of the red chili pests that plays a role as a Begomovirus vector. This vector can be controlled through Integrated Pest Management (IPM) practices. One of the potential practices is by utilizing corn as a barrier crop to prevent the vector from attacking the main crop. The aim of this research was to examine the repellence activity of the volatile compound obtained from various ages of corn crop against B. tabaci. The volatile compound was collected from the corns at 4 week after planting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Results from GCMS analysis of each maize variety revealed several compounds with repellent properties against B. tabaci, including 9-otadecenoic acid (Z)-, 9-octadecenamide, (Z)-, deltaguaiene, alpha-guaiene, beta caryophyllene, and patchouli alcohol. These findings corroborate results from Tyasningsiwi et al (2019) which identified citronella, limonene, β-phellandrene, β-caryophyllene, 1.8 cineole, farnesol, caryophyllene, and patchouli alcohol are repellent volatile compounds from maize against B. tabaci. 9-octadecenamide, (Z)-is known to possess larvicidal activities and disrupt insect respiration systems.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results from GCMS analysis of each maize variety revealed several compounds with repellent properties against B. tabaci, including 9-otadecenoic acid (Z)-, 9-octadecenamide, (Z)-, deltaguaiene, alpha-guaiene, beta caryophyllene, and patchouli alcohol. These findings corroborate results from Tyasningsiwi et al (2019) which identified citronella, limonene, β-phellandrene, β-caryophyllene, 1.8 cineole, farnesol, caryophyllene, and patchouli alcohol are repellent volatile compounds from maize against B. tabaci. 9-octadecenamide, (Z)-is known to possess larvicidal activities and disrupt insect respiration systems.…”
Section: Discussionsupporting
confidence: 89%
“…Further research is required to explore the potential of this approach and its practical application in pest management. Tyasningsiwi et al (2019) identified maize volatile compounds as B. tabaci repellents, specifically in Bisi-2. However, many maize varieties in Indonesia have been developed to produce different volatile compounds.…”
Section: Introductionmentioning
confidence: 99%